The Radio Source Population of Globular Clusters - Tudor, Vlad Andrei (Curtin University, 2018)
Globular clusters host a myriad of dynamically-formed objects, some of which may be black hole X-ray binaries. The existence of such systems in globular clusters has yet to be confirmed, but deep radio observations may efficiently find them. The MAVERIC survey was conceived with this goal in mind. In this thesis I present its results, highlighting black hole candidates, contrasting them with neutron star systems, and gauging their nature.